The host plants of Euura cinereae Kopelke, 1996 and E. auritae Kopelke, 2000 (Hymenoptera: Tenthredinidae) - Kopelke, Jens-Peter (Entomologica Fennica, 2002)
Euura auritae and Euura cinereae are distinct species making spindle-shaped stem galls on Salix aurita and on Salix cinerea, respectively. Different morphological criteria and no-choice as well as multiple choice oviposition experiments have proved E. auritae and E. cinereae to be distinct species. Euura cinereae on S. cinerea is distributed at least over Southern Norway, Germany and Austria, but within its distribution area it may occur patchily. A recent paper doubted that the type specimens of E. cinereae had been reared from S. cinerea, but rather that they had been reared from S. aurita. However, as discussed in the present paper, they give no convincing evidence that E. cinereae occurs on S. aurita rather than on S. cinerea in Finland.